Planning and implementation of medical support for a cross-country obstacle race. (January 2016) - Pearkes, Tim; Buckley, Andrew; Acharya, Mehool
Middle distance arduous outdoor events have risen in popularity over the last four years. This rise is accompanied by an increase in the number of injuries and anecdotally a rise in emergency department attendances. Event organisers are employing on-site medical teams to manage injured runners where possible and refer onwards appropriately when required. One such event is the WOLF RUN: a 10 km mud race with obstacles that provides runners of all abilities with a challenge. Events such as this require careful planning to reduce the risk of injury; however, should injury occur, this planning should lead to prompt assessment, treatment, and if necessary, evacuation. This article describes the event the medical planning that takes place prior each run, difficulties encountered and lessons learnt. We outline the requirements of a doctor taking on such an event, the medical resources and personnel required to safely staff it and the types of injury/illness that have been treated to date.